TINGKAT PENGETAHUAN IBU NIFAS TENTANG NUTRISI YANG DAPAT MENINGKATKAN PRODUKSI ASI DI BPS EDI SURYANINGRUM GODEAN SLEMAN YOGYAKARTA - Lisa Novita Sari; Eva Putriningrum (MEDIA ILMU KESEHATAN, 2016)
Background: In Indonesia, exclusive breastfeeding (a period of 6 months breastfeeding without additional intake) only covered 16.5% women. In 2013, Sleman reached a number of 80.62%. The ability to brestfeed exclusively is related to breastmilk production, which also corresponds with mothers’ nutritional status. It is necessary for puerperal mothers to have knowlegde about nutrition that increase breastmilk production. Objective: This study aimed to describe the level of knowledge of puerperal women about nutrition that can increase breastmilk production at BPS Edi Suryaningrum, Godean, Sleman, Yogyakarta. Methods: This study used descriptive quantitative research methods. Sample were selected with a total sampling, consisted of 44 puerperal women. Data were collected with a set of questionnaire, then analyzed with a univariate analysis. Results: Respondents varied, with a range of age at 20-35 years old, majority were graduates of high school and unemployed (housewife). Twenty two respondents (50.0%) had adequate knowledge about nutrition that can increase breastmilk production. Conclusion: The knowledge of puerperal women about nutrition that increase breastmilk production was majority in adequate level. Keywords: Knowledge of puerperal women, nutrition and breastmilk